Effect of Rice Cercosporidium Caused by Cercospora oryzae Miyake on the Productivity of TS2 and IR841 under Controlled Conditions - SOURA, HERVE; Koita, Kadidia; ZANDJANAKOU-TACHIN, MARTINE; GNANCADJA, ANDRÉ LÉOPOLD SIMPLICE; GOUDJO, Godefroy; SAVADOGO, Aly; BABA-MOUSSA, LAMINE SAÏD (My University, 2022)
Background and Objective: In Benin, rice production has increased significantly over the past five years. Despite this increase, numerous parasitic constraints, particularly fungal, contribute significantly to the decline in productivity, making the country dependent on imports. The present study aimed at improving the knowledge of Cercospora oryzae to increase rice yields. Materials and Methods: In a controlled environment, a trial was set up using a split-Plot design. Agro-morphological parameters were evaluated based on observations and measurements according to the IRRI 2002 scale. Results: The results obtained reveal a negative impact of Cercospora oryzae on rice productivity. Cercospora oryzae hurts seedling emergence rates. In TS2, seedling emergence rates ranged from 65.10-98.85% for seeds occulted with Cercospora oryzae and 97.85% for um inoculated seeds. Cercospora symptoms were observed on the leaves and stems of all plants except those not inoculated with varying degrees of severity. Conclusion: The average number of productive tillers decreased when inoculated early. Inoculation at the swelling and heading stages reduced the weight of 1000 grains. Cercosporidium negatively impacts rice growth and yield.
Keywords: Rice; Cercospora oryzae; disease; yield; degrees of severity